Rock Mass Assessment using Geological Strength Index (GSI) along the Ranau-Tambunan Road, Sabah, Malaysia - Norbert Simon, Rodeano Roslee, Abdul Ghani Rafek, Goh Thian Lai,, . (2016)
This study discusses the characterization of rock slopes along the 54 km road from Ranau to Tambunan (RTM), Sabah, Malaysia. Along this stretch, seven slopes were assessed, with two (B20 and B35) located in the Crocker Formation and the others (B4, B5, B7, B13 and B16) in the Trusmadi Formation. The Geological Strength Index (GSI) technique was used to characterize the weathering condition and rock structures of the slopes